Export marketing behaviour of resource-based firms in Malaysia - Mohamad, Osman; Wheeler, Colin N. (Universiti Utara Malaysia, 1997)
This article is concerned with the export market strategy adopted by manufacturers-exporters in resource-based industries. The characteristics, export performance and marketing strengths of firms adopting a market concentration srtrategy versus firms adopting a market diversification strategy are investigated. The results show that firms adopting a diversification strategy are larger, have more export experience and higher percentage of foreign equity participation, and achieved better export performance compared to firms adopting a market concentration strategy. The former also exhibits greater commitment to exporting and are significantly different from the latter as regards to sources of marketing competitive strengths.